PENGEMBANGAN TAMAN WISATA EDUKASI ROLAK BERBASIS SPOT FOTO - Irma Hidayati; Shofi Mustajibullah; Muhlas Septiawan; Inrah Wati Juwita; Dewi Nur Hayati; Selfiyah Selfiyah; Ziat Emilia Syafitrih; Anton Kurniawan; Amira Fajril Lutfiah; Muhammad Ilham Habibi; Nur Afidah (Universitas Islam Malang, 2022)
One of the tourist attractions of Malang City's Kedungkandang Village is Rolak Educational Park. The Kedungkandang community is in charge of managing and developing the park, which is located alongside the Amprong river. The appeal of Rolak Educational Park Tourism significantly decreased during the covid-19 pandemic. Increasing the viability of Rolak Educational Park Tourism as one of the tourist attractions in Kedungkandang Village, Malang City, is the goal of this act of community service. The approach employed is one of planning, carrying out, and supervising. A new icon at the Rolak Kedungkandang Educational Park was created as a result of this volunteer work in the community, which led to the creation of the first picture location. At the Rolak Educational Park, the creation of photo locations has boosted tourists' interest in exploring.